Sentinel lymph node biopsy in cutaneous melanoma – what we have done and where we go? - Pieńkowski, Andrzej; Nasierowska-Guttmejer, Anna; Sałamacha, Maciej; Rutkowski, Piotr; Jędrzejczak, Tomasz; Dziewirski, Wirginiusz; Ruka, Włodzimierz; I. Nowecki, Zbigniew; Żurawski, Zbigniew (Contemporary Oncology/Współczesna Onkologia, 2003)
Introduction: Sentinel lymph node (SLN) biopsy is a procedure being increasingly used for the diagnosis of cutaneous melanoma patients. The aim of the study was the analysis of failures of this method, the pattern of metastases and clinical outcome of patients with clinically uninvolved regional lymph nodes who have undergone SLN biopsy carried out in the Cancer Centre in Warsaw, Poland. Material and Method: Prospectively collected data of 934 consecutive patients with primary cutaneous malignant melanoma (355 males and 579 females; median age: 51, ranging from 15 to 84 yrs) who have undergone 1053 SLN regional basin biopsies between April 1995 and December 2002 were evaluated. The primary melanoma sites included the head and neck in 12 patients, the trunk in 385 patients, the upper extremities in 162 patients and the lower extremities in 375 patients. Median Breslow thickness was 2.85 mm. All patients were followed closely, the median follow-up time reaching 38 months for survivals. All patients underwent preoperative lymphoscintigraphy. The first 183 SLN biopsies in regional basins were performed with the vital blue dye technique (SLNB-PB) and the other 870 cases with the blue dye combined with intraoperative lymphoscintigraphy technique (SLNB-S). Results: The sentinel node (s) were successfully identified in 95.3% of regional basins (1003/1053). Intraoperative lymphoscintigraphy combined with the blue dye technique improved SLN identification rate (technical success in 97% of cases; 840/870), as compared to the blue dye only technique (technical success in 89%; 163/183; p 4 mm, male gender, more than one lymph node involvement and lymph node extracapsular extension. The estimated 5-year OS rate was 86% for SLN negative patients and 42% for SLN+ patients (p<0.0001). Conclusion: SLN biopsy is currently a valuable and reliable diagnostic procedure for precise staging of patients with clinically N0 cutaneous melanoma. The proper SLN biopsy procedure consists of operative identification of SLN (s) with the blue dye combined with intraoperative lymphoscintigraphy technique, dissection of SLN (s) and precise pathological evaluation of entire SLN (s). The presence of SLN metastases is the most important negative factor for clinical outcome in melanoma patients.